Management of spontaneous intracranial hypotension – Transorbital ultrasound as discriminator. Issue 6 (18th August 2015) - Fichtner, Jens; Ulrich, Christian T; Fung, Christian; Knüppel, Christin; Veitweber, Martina; Jilch, Astrid; Schucht, Philippe; Ertl, Michael; Schömig, Beate; Gralla, Jan; Z'Graggen, Werner J; Bernasconi, Corrado; et al.
Abstract : Objective: Spontaneous intracranial hypotension (SIH) is most commonly caused by cerebrospinal fluid (CSF) leakage. Therefore, we hypothesised that patients with orthostatic headache (OH) would show decreased optic nerve sheath diameter (ONSD) during changes from supine to upright position. Methods: Transorbital B-mode ultrasound was performed employing a high-frequency transducer for ONSD measurements in the supine and upright positions. Absolute values and changes of ONSD from supine to upright were assessed. Ultrasound was performed in 39 SIH patients, 18 with OH and 21 without OH, and in 39 age-matched control subjects. The control group comprised 20 patients admitted for back surgery without headache or any orthostatic symptoms, and 19 healthy controls. Results: In supine position, mean ONSD (±SD) was similar in patients with (5.38±0.91 mm) or without OH (5.48±0.89 mm; p=0.921). However, in upright position, mean ONSD was different between patients with (4.84±0.99 mm) and without OH (5.53±0.99 mm; p=0.044). Furthermore, the change in ONSD from supine to upright position was significantly greater in SIH patients with OH (−0.53±0.34 mm) than in SIH patients without OH (0.05±0.41 mm; p≤0.001) or in control subjects (0.01±0.38 mm; p≤0.001; area under the curve: 0.874 in receiver operating characteristics analysis). Conclusions: Symptomatic patients with SIH showed a significant decrease of ONSD, as assessed by ultrasound, when changing from the supine to the upright position. Ultrasound assessment of the ONSD in two positions may be a novel, non-invasive tool for the diagnosis and follow-up of SIH and for elucidating the pathophysiology of SIH.